2017
DOI: 10.1589/jpts.29.1229
|View full text |Cite
|
Sign up to set email alerts
|

The effects of progressive neuromuscular training on postural balance and functionality in elderly patients with knee osteoarthritis: a pilot study

Abstract: [Purpose] To determine the effects of progressive neuromuscular training on postural balance and functionality in elderly patients with knee osteoarthritis (OA). [Subjects and Methods] Eleven participants between 60 and 75 years of age performed the progressive neuromuscular training for 8 weeks and 4 weeks of follow-up. The area and velocity of the center of pressure were measured on a force platform, and the functionality was measured with a Western Ontario and McMaster Universities Osteoarthritis Index. [Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
1
4
0
3
Order By: Relevance
“…Also, knee OA as radiologically measured by means of the Kellgren-Lawrence score resulted in correlation to the average Stability Index in the open eyes trial, suggesting that a worse functional performance is present in more severe radiological OA. This finding confirms previous evidence of impaired postural stability in patients with osteoarthritis of the knee, especially those diagnosed with grade III or IV degeneration [6,17,20]. The worst performance of women in the clinical-functional scores, namely the KSS-F and SPPB scores, confirm a strong relationship between clinical and instrumental tests, in accordance with previous literature reporting higher levels of disability in females compared to males with knee OA [43].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Also, knee OA as radiologically measured by means of the Kellgren-Lawrence score resulted in correlation to the average Stability Index in the open eyes trial, suggesting that a worse functional performance is present in more severe radiological OA. This finding confirms previous evidence of impaired postural stability in patients with osteoarthritis of the knee, especially those diagnosed with grade III or IV degeneration [6,17,20]. The worst performance of women in the clinical-functional scores, namely the KSS-F and SPPB scores, confirm a strong relationship between clinical and instrumental tests, in accordance with previous literature reporting higher levels of disability in females compared to males with knee OA [43].…”
Section: Discussionsupporting
confidence: 91%
“…Literature has reported impairments in standing balance and proprioception in people with knee OA both through clinical tests [8,[15][16][17] and laboratory-based measurements [17][18][19][20]. These studies clearly show that the lack or the inappropriate proprioceptive information arising from the knee joint has a negative effect on static and dynamic balance control.…”
Section: Introductionmentioning
confidence: 88%
“…A possible reason for the protective effect may be that the quadriceps can attenuate loading during functional tasks (37). The quadriceps help maintain the dynamic stability of knee joint (38), and the process of strength training can reduce the long-term low-grade inflammation of the knee joint (39). Thus, more prospective, longitudinal studies are required to confirm the protective role of quadriceps strength.…”
Section: Discussionmentioning
confidence: 99%
“…Takacs et al in their study reported that dynamic balance training exercises benefitted OA knee patients by the significant reduction in pain, kinesiophobia, and improvement in their physical function. He-Sang et al also found that patients with moderate and severe OA demonstrate increased balance deficits than those with mild OA [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%